2021
DOI: 10.1109/tsp.2020.3046355
|View full text |Cite
|
Sign up to set email alerts
|

Cascaded Spline-Based Models for Complex Nonlinear Systems: Methods and Applications

Abstract: In this paper, we present a class of cascaded nonlinear models for complex-valued system identification, aimed at baseband modeling of nonlinear radio systems. The proposed models consist of serially connected elementary linear and nonlinear blocks, with the nonlinear blocks implemented as uniform spline-interpolated look-up tables (LUT) and the linear blocks as FIR filters. Wiener, Hammerstein, and Wiener-Hammerstein models are built, and simple but efficient gradient based adaptive learning rules are derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 41 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…Complex-valued adaptive filtering algorithm has a wide range of engineering applications in radio systems [ 1 ], system identification [ 2 ], environment signal processing [ 3 ], and other fields. Generally speaking, complex-valued adaptive filtering algorithm is an extension of the real-valued adaptive filtering algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Complex-valued adaptive filtering algorithm has a wide range of engineering applications in radio systems [ 1 ], system identification [ 2 ], environment signal processing [ 3 ], and other fields. Generally speaking, complex-valued adaptive filtering algorithm is an extension of the real-valued adaptive filtering algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 6 ] reported an adaptive estimator for the considered system where the adaptive law is designed through the usage of the parameter error and initial value. An efficient gradient estimation method is given in [ 13 ] by Campo et al . for the sandwich model, and the model is used to build a dynamic model of a nonlinear radio system.…”
Section: Introductionmentioning
confidence: 99%